Papers of Julian Lowell Coolidge, - Coolidge, Julian Lowell, 1873-1954. (Collections of the Harvard University Archives. Personal archives.)
These papers chiefly document Coolidge's personal life, wartime activities, and student life. They do not document Coolidge's administrative duties at Harvard.